The Impact of TikTok on Body Image: A Narrative Review of the Literature - Alamyar, Iqbal Hussain; Khotimah, Khusnul (CV. ITTC INDONESIA, 2023)
TikTok is a widely used social media platform that enables users to create and share short videos with music, using various filters and creative features. It has a large and diverse user base, especially among young people, who are particularly vulnerable to influences on body image. This study aims to review the existing literature on how TikTok influences users’ perceptions of their own bodies and those of others. A narrative review was conducted using various databases. The selection and screening of studies were based on predefined criteria, focusing on those that investigated the relationship between TikTok usage and body image perceptions. The review revealed a mixed impact of TikTok usage on body image perceptions. Several studies indicated that exposure to body-related content on TikTok could lead to negative body image and dissatisfaction among users. However, some studies suggested that TikTok could also be a platform for promoting body positivity and acceptance. The findings underscore the need for further research to understand the nuanced effects of TikTok on body image perceptions. And also highlights the potential of social media platforms like TikTok in shaping societal norms and attitudes toward body image Keywords: Social Media, TikTok, Body Image, Narrative Literature Review, Content Analysis